Grade students attending classes in primary schools and at gymnasiums at national mathematics competitions - Vulović Nenad R.; Milenković Aleksandar Z.; Milikić Milan P. (Zbornik radova (Univerzitet u Kragujevcu. Pedagoški fakultet u Užicu))
For decades, mathematics education researchers have been focusing on students with special abilities in mathematics and mathematics competitions, and examining the impact of various organizational forms of work, such as grouping students and enriching teaching and learning programs, on students' success in competitions. Considering the lack of similar research in the Republic of Serbia, as well as the tradition of grouping students with special abilities in mathematics into specialized (SM) classes, this study aimed to investigate whether there is a trend in the increased participation of SM class students in national competitions and to determine whether there are differences in the achievements of students from SM and regular classes. The research sample consists of all seventh and eighth-grade students who participated in national competitions from 2007 to 2024. The results indicate that there is a trend of increasing the number of SM class students in national competitions, as well as a statistical difference in the achievements of students attending regular and specialized mathematics classes in favor of students grouped in homogeneous (SM) classes. Moreover, over the past 18 years, SM class students have statistically significantly outperformed their peers 11 times in seventh and 12 times in eighth grade. Based on the obtained results, it can be concluded that grouping mathematically gifted students into homogeneous, specialized classes positively affects their performance in national competitions.